Assessment of microplastics in highland rock salts of Northern Borneo - Mohan Viswanathan, Prasanna; Mishra, Anshuman; Singam, Dayarnan Raj; John, J. (2024)
Mountain salts produced from the highland region in NE Sarawak have a market value and also provide basic income to the communities. During the salt-making process, microplastics (MPs) may enter into commercial table salts from various sources, which has not been explored yet. Hence, the current research investigates the presence of MPs in the rock salts produced from the highland saline water in two different locations (L1 and L2) in NE Sarawak. Among the brine water and rock salt samples analysed, the highest concentrations of MPs were detected from the salt samples. It has been revealed that both the water and salt samples have the highest concentration of MPs occurring within the size range of 1–1000 μm. Transparent MPs are the most common colour observed in both salt and water samples, followed by white, blue, red, and black. The most prevalent shapes of MPs are fibers, which account for almost 47% in water samples and 87% in salt samples. Based on the ATR-FTIR study, polyethylene (PE) is the most prevalent polymer observed in salt samples, followed by polypropylene (PP), polystyrene (PS), and polyethylene terephthalate (PET). In water samples, PP is the most dominating polymer, followed by PE and PS. Through SEM microphotographs, fiber-type MPs have smooth surfaces, fragment-type MPs have rough edges, and sheet-type MPs have layered surfaces. EDX analysis revealed that carbon (C) and oxygen (O) are the most abundant elements, followed by aluminium (Al) and sodium (Na) in MPs. Based on the results, it is inferred that the MPs in the rock salts are mainly sourced from the different stages of salt-making production. This preliminary study shed light on the presence and characteristics of MPs in rock salts in this region. The research outcomes could support sustainable management plans to improve the salt quality and enhance the market value.